1997
DOI: 10.1007/bf00941802
|View full text |Cite
|
Sign up to set email alerts
|

Detection of matrix metalloproteinase activity in human pancreatic cancer

Abstract: Destruction of the basement membrane (BM) is mandatory for tumor spread, and matrix metalloproteinases (MMPs) are known to be implicated in colon cancer invasion and metastasis by digesting type IV collagen, a main component of the BM. The current study analyzed the expression of MMP-2 and MMP-9 in pancreatic cancer tissues. Frozen specimens of pancreatic cancer (n = 10), a liver metastatic nodule from pancreatic cancer (n = 1), and normal pancreas (n = 3) were homogenized and analyzed by zymography. The activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 4 publications
3
20
1
Order By: Relevance
“…Using higher concentrations of SDF-1a (25 mM), a downregulation of the response was observed, which is probably due to CXCR4 downregulation [Koshiba et al, 1997]. LRRC4 could inhibit the SDF-1a-induced proliferation in U251/LRRC4 cells, compared with that in U251/mock cells (P < 0.01).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Using higher concentrations of SDF-1a (25 mM), a downregulation of the response was observed, which is probably due to CXCR4 downregulation [Koshiba et al, 1997]. LRRC4 could inhibit the SDF-1a-induced proliferation in U251/LRRC4 cells, compared with that in U251/mock cells (P < 0.01).…”
Section: Resultsmentioning
confidence: 72%
“…To determine the relative concentration and activity of gelatinases in the conditioned medium, SDS-PAGE gelatin zymography was performed by using a previously reported method [Koshiba et al, 1997]. Briefly, 40 ml of each conditioned medium was treated with SDS-PAGE sample buffer without boiling and reduction.…”
Section: Gelatin Zymographymentioning
confidence: 99%
“…MMP-2 expression is enhanced in pancreatic cancer in cells at the invasive front rather than in the tumor center [18]. Although MMP-2 expression in pancreatic cancer has been investigated in several studies by various methods, the prognostic role of MMP-2 yet has to be fully elucidated [16, 17,19,20,21]. The aim of this study was to evaluate the expression of MMP-2 and its prognostic value in 127 pancreatic ductal adenocarcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…MMPs are a group of calcium-and zinc-dependent proteases, and together with their inhibitor, tissue inhibitor of metalloproteinases (TIMPs), regulate tumor invasion and metastasis. Among them, MMP-2 and MMP-9 were found to be overexpressed in pancreatic cancer tissue and closely associated with tumor invasion and metastasis (8,9). In addition, Farrow et al (10) reported that the selective PPARγ agonist RGZ enhanced the expression of phosphatase and tensin homolog (PTEN) in pancreatic cancer AsPC-1 cells and inhibited AKT phosphorylation, while application of the PPARγ inhibitor GW9662 suppressed PTEN expression, suggesting that PPARγ ligands attenuate pancreatic cancer cell growth via inhibiting phosphoinositide 3-kinase (PI3K) activity through upregulating the expression of the tumor suppressor gene PTEN.…”
Section: Introductionmentioning
confidence: 99%